Effect of Bohm potential and magnetohydrodynamic wave propagation in Fermi degenerate quantum plasma - Garai, Sisir kr; Prajapati, R. P. (International Journal of Physical Research, 2013)
In this paper we have investigated the effect of Bohm potential and electron spin on the low frequency magnetohydrodynamic wave propagation in quantum plasma. The elementary ideal about quantum collision process is also discussed. The quantum magnetohydrodynamic (QMHD) model is modified and a general dispersion relation is obtained using the plane wave approximation. This dispersion relation is reduced for the parallel and perpendicular mode of propagations. We find that the motion of Fermion particles in presence of magnetic field show the scattering phenomena. The quantum Bohm potential is coupled with the Alfven mode in perpendicular propagation but in the parallel mode of propagation the dispersion relation is unaffected due to the presence of magnetic field. From the curves we find that increase in Alfven velocity and sound velocity increases the frequency of the perturbations.